2011
DOI: 10.1108/00035591111167703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic hydrostatic pressure on the sacrificial anode cathodic protection

Abstract: Purpose-The purpose of this paper is to study the effect of cyclic hydrostatic pressure on the protective performance of cathodic protection (CP) system consisting of Zn-Bi sacrificial anode and Ni-Cr-Mo-V steel. Design/methodology/approach-The anode and cathode polarization curves of the driving potential and current for CP were investigated in case of cyclic hydrostatic pressure (0-3.5 MPa) and compared with that at atmospheric pressure. The morphologies of the anode material with and without corrosion produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Aluminum (Al) alloy sacrificial anodes have been widely used to protect marine structures due to their high current efficiency, low specific weight, and low cost. [1][2][3][4][5] They usually work in the seawater at different depths [6][7][8][9][10] or sea mud, [11][12][13] displaying different electrochemical performances due to different media features, such as temperature, [14][15][16] hydrostatic pressure, [6][7][8][9][10] dissolved O 2 (DO) content, [14] pH, [17] and sulfate-reducing bacteria (SRB). [13,18,19] Nowadays, steel shell-concrete composite structure has been adopted for subsea immersed tunnels, typically buried in backfilled stone layers up to several meters thick and hundreds of kilograms per unit, as shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum (Al) alloy sacrificial anodes have been widely used to protect marine structures due to their high current efficiency, low specific weight, and low cost. [1][2][3][4][5] They usually work in the seawater at different depths [6][7][8][9][10] or sea mud, [11][12][13] displaying different electrochemical performances due to different media features, such as temperature, [14][15][16] hydrostatic pressure, [6][7][8][9][10] dissolved O 2 (DO) content, [14] pH, [17] and sulfate-reducing bacteria (SRB). [13,18,19] Nowadays, steel shell-concrete composite structure has been adopted for subsea immersed tunnels, typically buried in backfilled stone layers up to several meters thick and hundreds of kilograms per unit, as shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, subsea‐immersed tunnels apply a steel shell–concrete composite structure with heavy backfilled stone layers to fix the tunnels, as shown in Figure 1a, [ 1 ] where the steel shells are usually protected by anticorrosion coatings and aluminum (Al) alloy sacrificial anodes (Figure 1b). [ 2,3 ] Thus, the anodes and the steel shells are buried in inhomogeneous backfilled stone/brine media quite different from other media in the marine environment, such as seawater [ 4–8 ] or sea mud. [ 9–11 ] Preliminary research shows that the backfilled stone can inhibit the ions' diffusion, decrease the dissolved O 2 (DO) concentration, and protect the surface of the anode and cathode, changing their cathodic protection effect in the initial period.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu et al studied the effect of cyclic hydrostatic pressure on the sacricial anode CP, while little attention has been devoted to the formation of calcareous deposits on the cathode surface. 18 Thomason and Fischer suggested that it was not the hydrostatic pressure that causes the compound variation of calcareous deposits in deep water but the temperature and ow velocity, and the growth of calcareous deposits was mainly controlled by the ocean sites and eld environments. 19 Tawns and Oakley studied the CP at a simulated depth of 2500 m and found that thick but poorly adherent calcareous deposits were formed by high-pressure CP aer 30 d, and the protectiveness was not as effective as that found at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%